KAJIAN UNSUR INTRINSIK DAN NILAI PENDIDIKAN CERITA CEKAK DALAM MAJALAH JAYA BAYA SERTA RELEVANSINYA SEBAGAI BAHAN AJAR APRESIASI SASTRA JAWA KELAS X SEKOLAH MENENGAH ATAS - Sulistiyaningsih, Wahyu; Sumarwati, Sumarwati; Kurwidaria, Favorita (Universitas Sebelas Maret, 2019)
The aims of this study are to describe the intrinsic elements and education values of the short stories in Jaya Baya Magazine in the edition of August to October 2014, and to describe the relevance of the intrinsic elements and education value of the short sories in Jaya Baya Magazine as teaching materials in Javanese literature appreciation in Senior High School class X. The results showed that the majority themes in the short stories is traditional-based themes. The plot used by the authors in the short sories is chronological plot. The characters consist of the main characters and supporting characters. Characterizations raised through the physical, psychological, and social background. Psychical character was raised by expository and dramatic technique. The setting includes places, time, and social. The point of view which is majority used is first-person perspective. The messages which are conveyed are regarding to attitudes towards oneself, against others, and against God. Moral values are most numerous in Welingmu and Mbah Kakung. Social value in Welingmu and Oncating Cahya. Cultural values in Nglegok. Religious value in Welingmu, Mbah Kakung, and Oncating Cahya. Based on the results of the study on the intrinsic elements and education values, the short stories in Jaya Baya Magazine in the edition of August to October 2014 can be used as teaching materials Javanese literature appreciation in Senior High School Class X.